Covid-19 Vaccine Acceptance, Compliance and Adherence to Who Covid-19 Protocals among Health Care Workers in Homabay Town Sub County, Homabay County, Kenya - Akoth, Christine Obinju (JOOUST, 2022)
Health Care Workers are at the front line in the fight against Covid-19. The acceptance or otherwise of the Covid-19 vaccine by health care workers can influence the uptake of Covid- 19 vaccines among the general population as they are a reliable source of health information. With the fragile Health care system in low- and middle-income countries, Kenya being among them, the use of Covid-19 preventive measures is also strongly recommended and adherence to preventive measures of Coronavirus disease 2019 (Covid-19) was among the means to tackle the transmission of the virus. However, reluctance to implement the recommended preventive measures has been reported to be a major problem everywhere including in Healthcare workers. This study explored the acceptance of Covid-19 vaccine and compliance and adherence to WHO Covid-19 protocols among the healthcare workers in Homabay town Sub County, Homabay Kenya. The study was a cross-sectional web-based that was done between August 2022 to October 2022 among 300 health care workers where an online survey was used to collect data. Quantitative data was analyzed using SPSS version 23. Pearson’s Chi-square test was used to test for statistical significance between the categorical variables. Qualitative data was subjected to thematic analysis. The study recorded a response rate of 85.3%. The acceptance was at 98.8% however, there was delay in time to acceptance where 39.1% of HCWs were vaccine hesitant within the first six months of vaccine roll out. The study reported a 1.2% overall non-compliance rate to Covid-19 vaccine 18 months after vaccine roll-out. The HCWs stated vaccine side effects, safety concerns and low risk of getting Covid-19 as reasons for non-compliance Gender was significantly associated with vaccine hesitancy (p<0.043). On the four domains of adherence to Covid-19 prevention protocols, 37.5% did not adhere to handwashing ,51% did not avoid crowds ,48% did not adhere to donning of masks and 43.8% did not observe social distancing. In conclusion, the uptake was good however, there was a delay in time to acceptance and gender was significantly associated with vaccine acceptance. This study therefore recommends Homabay county to focus on male gender in case of any future vaccination drives and another study involving a larger cohort of different HCWs to ascertain the acceptance level since this study only focussed on nurses and clinical officers.
Keywords: Covid-19 Vaccine; Covid-19 Protocals